Collaborative Learning Model of MBKM Curriculum based on E-Learning of Narotama University - Arasy Alimudin; Agus Sukoco; Ani Wulandari; Sri Wiwoho Mudjanarko; Rusdianto Sesung; Moh. Saleh (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: The purpose of this study was to determine the collaborative learning model of the e-learning-based MBKM (Independent Learning Independent Campus) curriculum policy that is effective and able to ensure the achievement of the MBKM IKU No. 7 goal. Design/methodology/approach: This study uses a mix method approach employing a quantitative approach using crosstab and chi-square analysis, while a qualitative approach mobilizing interviews and FGDs. The research conducted is a survey because it includes the entire population as the object of research, the students who are directly or indirectly involved in the MBKM policy are 1633 people, while for lecturers are all 107 Narotama University lecturers. Findings: The results show of the crosstab analysis and chi-square test, it can be seen that from 16 MBKM policy indicators as many as 15 indicators have a significance value above 0.05, only one indicator is the indicator of knowing about the Independent Learning-Independence Campus (MBKM) policy and for Crostabs and ChiSuare analysis of the MBKM policy for Collaborative Learning and e-learning on the perception of e-learning in the form of a team based project method that supports the implementation of the MBKM policy shows that of the 16 MBKM policy indicators, 15 indicators have a significance value above 0. Paper types: Research paper